2006
DOI: 10.1002/cm.20124
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter, a newDrosophila protein associated with microtubules

Abstract: In this study we describe a novel Drosophila protein Jupiter, which shares properties with several structural microtubule-associated proteins (MAPs) including TAU, MAP2, MAP4. Jupiter is a soluble unfolded molecule with the high net positive charge, rich in Glycine. It possesses two degenerated repeats around the sequence PPGG, separated by a Serine-rich region. Jupiter associates with microtubules in vitro and, fused with the green fluorescent protein (GFP), is an excellent marker to follow microtubule dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 41 publications
3
110
0
1
Order By: Relevance
“…Robotics and automated microscopy were used to fix, stain, and image the cells (see Materials and Methods). The JW18 cell line expresses a GFP-Jupiter fusion protein that labels the cytoskeleton (Karpova et al 2006), thus highlighting the entire cytoplasm and indicating cell boundaries. Anti-histone staining labeled the host nuclei, and DAPI was used to stain both host nuclei and cytoplasmic Wolbachia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Robotics and automated microscopy were used to fix, stain, and image the cells (see Materials and Methods). The JW18 cell line expresses a GFP-Jupiter fusion protein that labels the cytoskeleton (Karpova et al 2006), thus highlighting the entire cytoplasm and indicating cell boundaries. Anti-histone staining labeled the host nuclei, and DAPI was used to stain both host nuclei and cytoplasmic Wolbachia.…”
Section: Resultsmentioning
confidence: 99%
“…The JW18 cell line bearing the Jupiter-GFP transgene was generated according to previously described methods (Karpova et al 2006;Serbus et al 2012;Debec et al 2016). Two-to 15-hour-old embryos derived from Wolbachia-infected flies carrying a Jupiter-GFP transgene were homogenized and plated in flasks.…”
Section: Generation Of Cultured Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the sets of such protein traps was obtained in Villefranche (France) by the team headed by A. Debec. Several chimeric proteins from this set have been characterized [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…To label the MTs, a Jupiter-GFP expressing protein trap line was used, a kind gift from Alain Debec. [Jupiter-GFP, -Jup-GFP for short -is a MT associated protein with thus far unknown function; Karpova et al, 2006]. The Jup-GFP provides better contrast MT images than any of the conventionally used Tau-GFP [Murray et al, 1998] or the Tubulin-GFP lines [Grieder et al, 2000] and does not effect viability and fertility perceptibly (data not shown).…”
Section: Drosophila Stocksmentioning
confidence: 94%